2021
DOI: 10.3389/fpsyt.2021.679379
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Personality Disorders: An Umbrella Review of Published Meta-Analyses of Case–Control and Cohort Studies

Abstract: The putative risk/protective factors for several personality disorders remain unclear. The vast majority of published studies has assessed personality characteristics/traits rather than disorders. Thus, the current umbrella review of meta-analyses (MAs) aims to systematically assess risk or protective factors associated with personality disorders. We searched PubMed–MEDLINE/PsycInfo databases, up to August 31, 2020. Quality of MAs was assessed with AMSTAR-2, while the credibility of evidence for each associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Although not explicitly raised by participants in this study, Trauma Informed Care principles may be relevant for addressing participants’ concerns, including stigma, poor engagement with the care system, and the need to feel supported and understood [ 61 ]. Research indicates the vast majority of those with BPD have suffered trauma, with a 13-fold greater likelihood of childhood trauma [ 62 ], aligning with research identifying trauma as both a risk factor and predictor BPD onset [ 63 , 64 ]. While trauma is neither necessary nor sufficient for BPD development, the effects of trauma can complicate BPD and its treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Although not explicitly raised by participants in this study, Trauma Informed Care principles may be relevant for addressing participants’ concerns, including stigma, poor engagement with the care system, and the need to feel supported and understood [ 61 ]. Research indicates the vast majority of those with BPD have suffered trauma, with a 13-fold greater likelihood of childhood trauma [ 62 ], aligning with research identifying trauma as both a risk factor and predictor BPD onset [ 63 , 64 ]. While trauma is neither necessary nor sufficient for BPD development, the effects of trauma can complicate BPD and its treatment.…”
Section: Discussionmentioning
confidence: 98%
“…As a matter of fact, during the pandemic year, a spread of psychological problems in children with an increased prevalence of symptoms like anxiety, fearness, and breathing difficulties have been reported [21][22][23][24][25]. Singh et al, in a recent review on the impact of COVID-19 on the mental health of children, showed high levels of stress, insomnia, poor appetite, and inattentiveness [26]. Xie et al, moreover, found that 22.6% and 18.9% of children and preadolescents in Hubei reported symptoms of depression and anxiety independently of demographic characteristics [27].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, regardless of age, many have suffered from isolation and loneliness, as mentioned earlier. A comparative study of child and adolescent mental health in 59 countries (COH-FIT for short) demonstrated the severity of problems and the need to closely monitor recent trends (Solmi et al, 2022).…”
Section: Youth Vs Elderly During the Covid-19 Pandemicmentioning
confidence: 99%